Incidence of forcing factors on land covers of the Guacheneque Paramo, Colombia - Yulia Ivanova; David H. Arenas; Julian G. Castellanos (Geography, Environment, Sustainability)
Paramo ecosystems are unique and are located in Ecuador, Colombia, and Venezuela. Although the Colombian government has made efforts for their preservation and sustainable use, several of the national paramos have experienced a change in their land cover as a result of climate variability, climate change, and the expansion of the agricultural and livestock frontiers. Changes in land cover can affect ecosystem integrity and its environmental services. Taking into account the regional importance of the Guachaneque paramo, it was analyzed whether its vegetation cover experiences any significant changes. This study was carried out by combining multi – temporal analysis of vegetation cover with climatic and statistical analyses. It was found that most land covers present a change mostly associated with human interventions (0.77–0.91). Climate variability and climate change also affect the landscape, but to a lesser extent (0.09–0.23). Water availability directly affects the expansion of all land covers, except paramo grassland, which indicates that an increase in rainfall associated with climate change will cause a contraction of this land cover. Currently, it is identified that anthropogenic pasture and crop surfaces replace the paramo grassland covers with an approximate change of 28.5 hectares per year. These results alert us to the need for monitoring and controlling the development of livestock and agricultural activities in order to preserve the integrity of the paramo landscape.